Primary Hydatid Cyst of Umbilicus, Mimicking an Umbilical Hernia - Mohammadreza Tarahomi; Hamidreza Alizadeh Otaghvar; Nazila hasanzadeh Ghavifekr; Daryanaz Shojaei; Farhood Goravanchi; Amir Molaei (Case Reports in Surgery)
Hydatid cyst caused by Echinococcus granulosus demonstrates an endemic infection in several countries such as Middle Eastern countries. Liver is the most frequently involved organ, followed by the lung. The case we present is solitary primary localization of cyst in abdominal wall which is extremely rare. A 57-year-old woman presented with an abdominal wall lesion in umbilical area that had been evolving for about 2 years with recent complaint of pain and discomfort. We detected a midline abdominal mass 12⁎13 centimeters in diameter which was bulged out in umbilicus. Preoperative clinical diagnosis of incarcerated umbilical hernia was made due to its physical examination while surgical exploration disproved the primary diagnosis and we found cystic mass adherent to superficial fascia without any communication to peritoneal space. The cyst was excised completely without any injury or perforation of containing capsule. The diagnosis of hydatid cyst was confirmed by histopathological examination of specimen. The retrograde evaluation showed no involvement of other organs. The patient was followed for two years and no recurrence of hydatid disease has been observed. Hydatid cyst should be considered as a differential diagnosis of abdominal wall and umbilical lesions especially in endemic regions.